Circulating Tumor Cells as a Prognostic Factor in Recurrent or Metastatic Head and Neck Squamous Cell Carcinoma: The CIRCUTEC Prospective Study. (1st October 2019) - Garrel, Renaud; Mazel, Martine; Perriard, Françoise; Vinches, Marie; Cayrefourcq, Laure; Guigay, Joël; Digue, Laurence; Aubry, Karine; Alfonsi, Marc; Delord, Jean-Pierre; Lallemant, Benjamin; Even, Caroline; et al.
Abstract: BACKGROUND: This prospective multicenter study evaluated the prognostic value of circulating tumor cells (CTCs) in relapsing nonoperable or metastatic head and neck squamous cell carcinoma (rHNSCC) treated by chemotherapy and cetuximab. METHODS: In 65 patients suitable for analyses, peripheral blood was taken at day 0 (D0 ) D7, and D21 of treatment for CTC detection by CellSearch ®, EPISPOT, and flow cytometry (FCM). Progression-free survival (PFS) was assessed with the Kaplan–Meier method and compared with the log-rank test ( P < 0.05). RESULTS: At D0, CTCs were detected with EPISPOT, CellSearch, and FCM in 69% (45/65), 21% (12/58), and 11% (7/61) of patients, respectively. In the patients tested with all 3 methods, EPISPOT identified 92% (36/39), 92% (35/38), and 90% (25/28) of all positive samples at D0, D7, and D21, respectively. Median PFS time was significantly lower in ( a ) patients with increasing or stable CTC counts (36/54) from D0 to D7 with EPISPOT EGFR (3.9 vs 6.2 months; 95% CI, 5.0–6.9; P = 0.0103) and ( b ) patients with ≥1 CTC detected with EPISPOT or CellSearch ® (37/51) ( P = 0.0311), EPISPOT or FCM (38/54) ( P = 0.0480), and CellSearch or FCM (11/51) ( P = 0.0005) at D7 . CONCLUSIONS: CTCs can be detected before and during chemotherapy in patients with rHNSCC. D0 –D7 CTC kinetics evaluated with EPISPOT EGFR are associated with the response to treatment. This study indicates that CTCs can be used as a real-time liquid biopsy to monitor the early response to chemotherapy in rHNSCC. ClinicalTrials.gov Identifier: NCT02119559